Comparative analysis on the sorption kinetics and isotherms of fipronil on nondegradable and biodegradable microplastics. (November 2019) - Gong, Wenwen; Jiang, Mengyun; Han, Ping; Liang, Gang; Zhang, Tingting; Liu, Guannan
Abstract: Biodegradable plastics have been introduced and widely used as a promising alternative to traditional nondegradable plastics. However, the differences in sorption behavior of pesticides on nondegradable and biodegradable microplastics has been insufficiently studied. Here, four types of nondegradable [polyethylene (PE), polystyrene (PS), polyvinyl chloride (PVC), polypropylene (PP)] and two types of biodegradable [polylactic acid (PLA), polybutylene succinate (PBS)] microplastics were selected to investigate the sorption mechanism of fipronil based on their sorption kinetics and isotherms. The results indicated that the sorption rates of PLA and PBS were much higher than those of PE, PP, PVC and PS and that the sorption capacities of fipronil on microplastics followed the order of PBS > PLA > PP > PE > PS > PVC. The sorption kinetics followed a pseudo-second-order kinetics model ( R 2 = 0.953–0.998) for all tested microplastics. External mass transport and intraparticle diffusion were the main rate controlling steps of the sorption of fipronil on microplastics. Furthermore, isotherm results indicated that a Langmuir model provided the best fit for fipronil sorption on PE, PS, PVC and PP ( R 2 = 0.997–0.999), while a Freundlich model was the most appropriate model for PLA and PBS ( R 2 = 0.998–0.999). The presence of surface O-containing functional groups and the spatial arrangement of rubbery domains are likely to affect the sorption process. The results from this work suggest that microplastics, especially biodegradable ones, may play an important role in the fate and transport of pesticides, and their effects on soil organisms ( e.g., earthworms) require further investigation. Graphical abstract: Image 1 Highlights: Sorption of fipronil on different MPs were studied based on their sorption kinetics and isotherms. The sorption kinetics followed a pseudo-second-order kinetics model for all tested MPs. Langmuir and Frenudlich model fitted best for nondegradable and biodegradable MPs, respectively. Sorption rates and capacities of biodegradable MPs were higher than those of nondegradable MPs. The presence of oxygen functional groups and rubbery domains are likely to affect sorption process. Abstract : This study highlights the differences in sorption capacity and mechanism of fipronil on nondegradable and biodegradable microplastics based on their sorption kinetics and isotherms. .